Awareness of aflatoxin and willingness to pay for aflasafe technology among maize farmers in Cibitoke, Makamba and Bujumbura Provinces in Burundi - Nduwimana, D.; Nwenjeri, G.; Bett, E.; Atehnkeng, J. (2024)
Purpose of the Study: This study aimed to assess the awareness of aflatoxin among maize farmers in Burundi and their willingness to pay for Aflasafe technology, with a focus on the provinces of Bujumbura, Cibitoke, and Makamba. Methodology: The study combined qualitative and quantitative techniques. Data collection involved households selected with the assistance of local administration, targeting male and married farmers with primary education and incomes below 100,000 Burundian Francs. Econometric software was utilized to analyze the data, and the contingent valuation method (CVM) was employed to capture farmers' willingness to pay. Findings: The study found that most maize farmers in the designated provinces married, and primarily educated, with incomes under 100,000 Burundian Francs. Many belong to organizations, are middle-aged, and support households of six. Despite limited knowledge of aflatoxin, there is a notable willingness to invest in Aflasafe technology. Conclusion: The study concludes that there is a notable lack of awareness among maize farmers in Burundi regarding aflatoxin contamination and its associated risks. Recommendation: The study recommends that the government develop and implement awareness programs to educate maize farmers about aflatoxin and promote the adoption of Aflasafe technology.